Morphological variability of the Hermann's tortoise (Testudo hermanni) in the Central Balkans - Katarina Ljubisavljević; Georg Džukić; Tanja Vukov; Miloš Kalezić (Acta Herpetologica, 2012)
Variation in a number of morphological characters were analysed in five populations of Testudo hermanni from Serbia and Montenegro. Tortoises from Serbia appeared significantly larger than those from Montenegro. An insular population of Montenegro was distinct due to its extremely small body size and mass and dark plastral pigmentation. Although the majority of tortoises had the supracaudal scute divided, many tortoises had the scute undivided. Effects of possible genetic divergence and/or adaptation to different environmental conditions on observed morphological variation were discussed.